Análise da estrutura e identificação de proteínas da cromatina nuclear espermática de bovinos - Morandi Filho, Romualdo (2013)
The sperm nuclear chromatin structure is a specific, complex, and that has not been fully elucidated. This study aimed to isolate this structure and evaluate its composition, as well as analyze their morphology. Purification of chromatin was performed by removing the cell membrane and nuclear envelope followed by a decondensation of resulting chromatin. Its molecular composition was analyzed by biophysical techniques of electrophoresis, highperformance liquid chromatography and mass spectrometry. And its morphology was analyzed by transmission electron microscopy. The results showed a protein composition rich in variants of histone H2B, keratin, and a reverse transcriptase and a nucleoporin of 50 kDa. The micrographs showed a structure that looks like a nuclear lamina and nuclear matrix fibers, a toroidal structures intertwined with this mesh of fibers in a more concentrated near the nuclear lamina, and a rod-shaped structure at the center of major axis of the head sperm that bound to the fibers and the matrix toroids similarly to the nuclear lamina.